Stan rozpoznania stanowisk zagrożonych i chronionych gatunków flory na przykładzie leśnictwa Sokołowice (Nadleśnictwo Oleśnica) - Gorzelak, Piotr (Leśne Prace Badawcze, 2012)
This article is an attempt to draw attention to the differentiation used to conserve endangered and protected species of flora in an area that is administered by the management board of the State Forests. I also draw attention to areas of insufficient knowledge of this subject-matter. A detailed inventory of endangered and protected species of flora for the purpose of planning in forestry would be very useful in light of laws related to nature conservation and the problem of preserving biological diversity. Research in the forest administration region of Sokołowice indicates that almost 2/3 (65.16%) of all sites harbouring endangered and protected species of flora are new (previously undocumented), despite the existence of numerous protected areas – this fact indicates that there are great research possibilities in this field. The main conclusion from this research confirms that multifunctional forestry in Poland will provide the greatest opportunity to preserve the widespread and numerous sites holding endangered and protected species of flora in economically important forests.